ENVIRONMENT AND HEALTH LIFESTYLES: STRUCTURAL AND INTERSECTIONAL ASPECTS OF HEALTH AND ILLNESS IN MEDICAL SOCIOLOGY - N. Georgieva-Stankova (Trakia Journal of Sciences)
Purpose and Methods: The paper traces the effects of the environment and other structural factors on individual health and illness, as analysed theoretically by Medical Sociology. More particularly, it focuses on the interplay between structural factors in sociology and individual agency, i.e. the extent to which one’s health is a matter of personal choice or affected by macrosocial factors, such as living conditions, social status, race/ethnicity, gender, age and etc. Results: An imaginary debate between an expanded economic view on health (Becker 1979) and a sociological perspective (Cockerham 2013) is staged to weigh out different standpoints and the insistence on the primacy of either of the factors. William Cockerham’s health lifestyles (2013) is analysed (an extension of the traditions of Max Weber and Pierre Bourdieu), as an interplay between life chances and life choices, stressing the primacy of structural factors, without disregarding individual agency, however, within the confines of particular structural restrictions. Discussion and conclusion: Criticism of Becker’s economic health perspective is provided. Additionally, the intersectionality of structural factors is examined and their mutual co-determination. Finally, a claim is made for the need to connect environmental health with preventive medicine.